CULTURAL COMMODIFICATION AND ITS IMPLICATION IN TOURISM: SYSTEMATIC LITERATURE REVIEW - Erwen, Ivana Valencia; Shielline, Patricia; Poluan, Regina Calista; Wangsa, Vanessa; Pratama, Wisnu; Widyawan, Indria (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2025)
AbstractCommodification refers to the process of transforming goods, services, ideas, or cultural practices into commodities that can be bought, sold, or traded in the market. This process often alters cultural traditions to meet market demands. This literature review examines how tourism commodifies cultural practices, frequently stripping them of their original meanings and significance. The review aims to explore the impacts and implications of this transformation on the broader tourism market by analyzing various theoretical frameworks. Our objectives include understanding how commodification occurs in different contexts, evaluating its effects on cultural identity and traditional practices, and identifying strategies to preserve cultural heritage while promoting sustainability in tourism development. Based on previous research on cultural commodification and its effects, future strategies should focus on creating authentic cultural experiences that educate visitors, enrich local communities, and protect traditions from the pressures of commercial interests.AbstrakKomodifikasi mengacu pada proses mengubah barang, jasa, ide, atau praktik budaya menjadi komoditas yang dapat dibeli, dijual, atau diperdagangkan di pasar. Proses ini sering mengubah tradisi budaya untuk memenuhi permintaan pasar. Tinjauan literatur ini meneliti bagaimana pariwisata mengkomodifikasi praktik budaya, sering kali menghilangkan makna dan signifikansi aslinya. Tinjauan ini bertujuan untuk mengeksplorasi dampak dan implikasi dari transformasi ini pada pasar pariwisata yang lebih luas dengan menganalisis berbagai kerangka teoritis. Tujuan kami termasuk memahami bagaimana komodifikasi terjadi dalam konteks yang berbeda, mengevaluasi dampaknya terhadap identitas budaya dan praktik tradisional, dan mengidentifikasi strategi untuk melestarikan warisan budaya sambil mempromosikan keberlanjutan dalam pengembangan pariwisata. Berdasarkan penelitian sebelumnya tentang komodifikasi budaya dan efeknya, strategi masa depan harus berfokus pada menciptakan pengalaman budaya otentik yang mendidik pengunjung, memperkaya komunitas lokal, dan melindungi tradisi dari tekanan kepentingan komersial.